Contemporary Japanese thought - Calichman, Richard (Weatherhead books on Asia., 2005)
Appearing for the first time in English, the writings in this collection reflect some of the most innovative and influential work by Japanese intellectuals in recent years. The volume offers a rare and much-needed window into the crucial ideas and positions currently shaping Japanese thought (shiso). In addressing the political, historical, and cultural issues that have dominated Japanese society, these essays cross a range of disciplines, including literary theory, philosophy, history, gender studies, and cultural studies. Contributors examine Japan's imperialist and nationalist p.